1995
DOI: 10.1111/j.1365-277x.1995.tb00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment in energy intake following the covert removal of sugar from the diet

Abstract: The response to the covert removal of around 500 kcal/d from the food of 10 healthy free-living male volunteers was measured over 10 days. A similar amount of energy was added to the food of four subjects. Normal food and drink was available ad libitum, and adjustments in food energy were made by the interchange of sugar and artificial sweeteners. Compensation for the theoretical energy deficit or surplus was incomplete, averaging around 50%. This, however, was very variable, some subjects achieving more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 9 publications
2
39
0
Order By: Relevance
“…Careful experimental studies are required to examine the effects of varying the sugars (and starch) content of the diet on ED and also on energy intake. One such study whose results support the present ®ndings has shown that the covert removal of sugar from the diet actually raised the energy density 13 because sugars tended to be replaced by fat and protein. The restoration of sugar to the diet had the opposite effect.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Careful experimental studies are required to examine the effects of varying the sugars (and starch) content of the diet on ED and also on energy intake. One such study whose results support the present ®ndings has shown that the covert removal of sugar from the diet actually raised the energy density 13 because sugars tended to be replaced by fat and protein. The restoration of sugar to the diet had the opposite effect.…”
Section: Discussionsupporting
confidence: 79%
“…Some mis-reporting is inevitable in any dietary survey, but adjusting for energy in the present analysis should have minimized distortions; there is little evidence to suggest underreporting is macronutrient-speci®c. The methodology of the survey itself is detailed elsewhere, 13 but brie¯y, food intakes were assessed from 4-day weighed dietary diaries (n 1675) completed by the child's main carer. Energy and nutrient intakes, including NME sugars, were calculated by the original investigators using the Ministry of Agriculture, Fisheries and Food database of 6000 foods, which included home-made recipes, infant foods and branded items.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it may be difficult to prevent sweetener use over a long period of time in a participant who has been randomized to a no sweetener group. Out of dozens of works dealing with intense sweeteners' role in human nutrition, the meta-analysis addressed 15 RCTs with 24-h intake data (Porikos et al, 1977(Porikos et al, , 1982Foltin et al, 1988Foltin et al, , 1990Evans, 1989Evans, , 1992Mattes, 1990a;Tordoff and Alleva, 1990b;Naismith and Rhodes, 1995;Blackburn et al, 1997;Gatenby et al, 1997;Lavin et al, 1997;Reid and Hammersley, 1998;Raben et al, 2002;Van Wymelbeke et al, 2004) and nine RCTs with body weight data (Porikos et al, 1977(Porikos et al, , 1982Tordoff and Alleva, 1990b;Kanders et al, 1990;Naismith and Rhodes, 1995;Blackburn et al, 1997;Gatenby et al, 1997;Reid and Hammersley, 1998;Raben et al, 2002). These RCTs showed considerable variations in their design, study population, duration and type of control.…”
Section: The Use Of Intense Sweeteners In the Free-living Populationsmentioning
confidence: 99%
“…Thus, maintenance of sugar intake should help to depress fat intake. Conversely, a reduction in sugar intake may bring about a concomitant passive increase in fat intake (Naismith & Rhodes, 1995). Second, sugar may improve the palatability of low-fat diets enabling better long-term compliance.…”
Section: Reducing Consumption Of Sugar-containing Foodsmentioning
confidence: 99%